2012
DOI: 10.1371/journal.pone.0033765
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Outcomes in Malawi, a Country with High Prevalence of HIV: A Prospective Follow-Up Study

Abstract: BackgroundStroke contributes significantly to disability and mortality in developing countries yet little is known about the determinants of stroke outcomes in such countries. 12% of Malawian adults have HIV/AIDS. It is not known whether having HIV-infection alters the outcome of stroke. The aim of this study was to document the functional outcome and mortality at 1 year of first-ever acute stroke in Malawi. Also to find out if the baseline variables, including HIV-infection, affect the outcome of stroke.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
89
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 16 publications
14
89
2
2
Order By: Relevance
“…This was a substudy of the Stroke Outcomes in Malawi (SOMA) study 16 , which was conducted by the Queen Elizabeth Central Hospital (QECH, Blantyre) medical department from August 2008 until April 2010. Patients were eligible for SOMA if they were aged 18 years or older and had a first-ever acute stroke within seven days before admission.…”
Section: Study Context and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a substudy of the Stroke Outcomes in Malawi (SOMA) study 16 , which was conducted by the Queen Elizabeth Central Hospital (QECH, Blantyre) medical department from August 2008 until April 2010. Patients were eligible for SOMA if they were aged 18 years or older and had a first-ever acute stroke within seven days before admission.…”
Section: Study Context and Settingmentioning
confidence: 99%
“…Patients without brain imaging were defined as having an undetermined stroke type. More detailed methods for case management, baseline assessment, and follow-up for the SOMA study are explained elsewhere 16 .…”
Section: Study Context and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, observational studies in other developing countries have suggested an association between immune dysfunction and stroke based on increased hospital admissions for young immunosuppressed HIV-positive patients with ischemic stroke in the absence of other obvious risk factors of ischemic stroke. (Tipping et al, 2007a;Heikinheimo et al, 2012). This suggests the role of degree of immunosuppression as a determinant of development of neurological manifestation of HIV/AIDS.…”
Section: Discussionmentioning
confidence: 96%
“…По данным исследований [22,46] -(39±8) лет. Одна из возможных причин уменьшения возраста пациентов с ВИЧ-инфекцией -отсутствие или недостаточность АРВТ [47,48].…”
Section: ишемические нарушенияunclassified